Stonewall Jackson : the man, the soldier, the legend - Robertson, James I., Jr. (James Irvin), 1930-2019. (New York : Macmillan Pub. USA ; London : Prentice Hall International, 1997)
A biography focusing on Jackson as an individual as well as a military strategist and general, by one of the country's leading Civil War historians. The passage of 130 years has only deepened the fascination and reverence for Confederate general Thomas Jonathan "Stonewall" Jackson. He ranks today as among the half-dozen greatest soldiers that America has produced. Military academies in both hemispheres still teach his tactics. Revered by his men, respected by his foes, Jackson became seemingly invincible. When he learned of the general's fatal wound, Robert E. Lee sent his "affectionate regards", saying, "He has lost his left arm but I my right arm". Jackson's early death in 1863 was the greatest personal loss suffered by the Confederacy and one that permanently crippled the wartime South. This eagerly awaited biography is based on years of research into little-known manuscripts, unpublished letters, newspapers, and other primary sources. It offers for the first time a complete portrait--not only of Jackson the brilliant military strategist and beloved general but also of Jackson, the man of orphaned background, unyielding determination to conquer adversity, and deep religious convictions. Includes b&w photos.
Struggles of an orphan -- Coming of age at west point -- Mexico and a hero's mantle -- Health, baptism, and controversy -- Establishing roots in lexington -- God and "Dearest Ellie" -- Search for oneself -- Home life gives way to war -- Virginia drillmaster -- Emergence of "Stonewall" -- Stormy road to a resignation -- The lessons of Kernstown -- "A crazy fool" -- Encouraging hope -- Victory in the valley -- Fatigue -- Duty -- Recovery at Cedar Mountain -- Stonewall at Manassas, part 2-- Death around a Dunker church -- Leading a corps -- Problems and pleasures of winter -- The greatest march -- Crossing the river -- Epilogue.
Includes bibliographical references (pages 763-787) and index.
Keywords: Jackson, Stonewall, -- 1824-1863.; Generals -- Confederate States of America -- Biography; Confederate States of America. -- Army -- Biography; Jackson, Stonewall, -- 1824-1863; Confederate States of America. -- Army; Generals; United States -- Confederate States of America; Jackson, Stonewall; Biographie; Biography